Possibility of Community Transmission of COVID 2019 Infection In India: A WTSO Analysis Outcomes - Sanjeev Davey; Anuradha Davey; Rajesh Jain (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Background: With modest 1.3% of GDP spent on health, India is yet to develop robust primary care, quality emergency response infrastructure, and a surveillance system which can manage COVID 2019 infections Community Transmission with Corona +ve load of 8360 by 15th April 2020. Objective: So a Study of analysis of available cases pointing towards Community Transmission is urgently needed in India by new kind of WTSO analysis approach.  Material & methods: As per latest articles available in Websites, search of various studies in any form ;using 3 key search words: ", Community Transmission, COVID 2019 Infection, Indian Cases" was done using websites of Google, PubMed, EMBASE, MEDLINE, Global Health, Psyc‑INFO, Biomed‑Central, Web of Science, Cochrane Library, world library ‑ World‑Cat, from 1 January, 2020 to 15th April 2020 by summarising information of available Indian Cases.  Results: Available 22 Indian cases analysis Including (18) HOT Spots cases in Literature reveals that with no international travel history or history of no contacts, moreover cases hiding and escapes from Isolation wards raises a Point of Possible budding of Community transmission in India, but nothing can be said very conclusively.  Conclusion: Although experts at the ICMR feel that,while, India is at stage 2 now, stage 3 of community transmission have not yet come out. But if strict lockdown related precautions such as social distancing are not taken seriously by general public, stage 3 may come soon in India as evident from our analyses by a WTSO approach applied on available cases.